Quantification of straylight induced by silicone oil adherent to intraocular lenses of different materials - Hammer, Maximilian; Britz, Leoni; Schickhardt, Sonja; Lieberwirth, Ingo; Munro, Donald; Uhl, Philipp; Scheuerle, Alexander F.; Khoramnia, Ramin; Łabuz, Grzegorz; Auffarth, Gerd U. (American journal of ophthalmology, 2024)
PURPOSE: A complication of using silicone oil as an intraocular endotamponade is its adhesion to intraocular lenses (IOLs). Forward light scattering is a measure to quantify the optical disturbance caused by adherent oil droplets. We tested the straylight caused by silicone oil adhesion to different IOLs and examined whether an approved cleaning solution, F4H5, reverses the induced straylight. - DESIGN: An experimental study. - METHODS: Two hydrophobic acrylic IOL models and 1 hydrophilic model with a hydrophobic surface (n = 8 per model: 24 lenses) had straylight measured before contact with silicone oils, providing a baseline for subsequent testing: 12 lenses with lighter-than-water silicone oil (Siluron 2000) and 12 with heavier-than-water oil (Densiron 68). The final measurement was performed after cleansing with F4H5 when we used scanning electron and light microscopy to detect surface changes. - RESULTS: Straylight was majorly increased in IOLs with adherent silicone oil (baseline vs adherent oil median 3.1 [2.1, 3.9] and 39.7 [22.7, 87.8] deg2/sr, respectively; P < .001). No difference was seen between heavier- and lighter-than-water silicone oils. Between IOL types, induced straylight varied significantly, with 1 hydrophobic model reaching the highest average straylight. F4H5 significantly reduced straylight values in all IOL types (median 9.4 [5.4, 13.8] deg2/sr). The microscopy revealed surface changes on the IOLs even after cleaning. - CONCLUSIONS: Silicone oil adhesion to IOLs can induce amounts of straylight known to cause severe optical disturbance. F4H5 cleansing solution reversed straylight values to only slightly increased values. We found no difference in straylight formation between the lighter- and heavier-than-water silicone oils.